Association between tocilizumab and emerging multidrug-resistant organisms in critically ill patients with COVID-19: A multicenter, retrospective cohort study - Ohoud Aljuhani (BMC, 2021)
Abstract Background Tocilizumab is an IgG1 class recombinant humanized monoclonal antibody that directly inhibits the IL-6 receptor. Several randomized clinical trials have evaluated its safety and efficacy in patients with coronavirus disease 2019 (COVID-19), and these studies demonstrate conflicting results. Our study aimed to determine the association between tocilizumab treatment and microbial isolation and emergence of multidrug-resistant bacteria in critically ill patients with COVID-19. Methods A multicenter retrospective cohort study was conducted at two tertiary government hospitals in Saudi Arabia. All critically ill patients admitted to intensive care units with a positive COVID-19 PCR test between March 1 and December 31, 2020, who met study criteria were included. Patients who received tocilizumab were compared to those who did not receive it. Results A total of 738 patients who met our inclusion criteria were included in the analysis. Of these, 262 (35.5%) received tocilizumab, and 476 (64.5%) were included in the control group. Patients who received tocilizumab had higher odds for microbial isolation (OR 1.34; 95% CI 0.91–1.94, p = 0.13); however, the difference was not statistically significant. Development of resistant organisms (OR 1.00; 95% CI 0.51–1.98, p = 0.99) or detection of carbapenem-resistant Enterobacteriaceae (CRE) (OR 0.67; 95% CI 0.29–1.54, p = 0.34) was not statistically significant between the two groups. Conclusions Tocilizumab use in critically ill patients with COVID-19 is not associated with higher microbial isolation, the emergence of resistant organisms, or the detection of CRE organisms.